Actions to transform food systems under climate change: Reduce food loss and waste - Transforming Food Systems Under a Changing Climate Initiative (2020)
Transforming Food Systems Under a Changing Climate is an initiative that aims to identify high-priority actions for food systems to both adapt to climate change and reduce emissions, while not losing sight of the many other functions of, and challenges to, our food systems. The action described in this briefing is one of 11 transformative actions that should take priority. In 2013, 1.7 Gt of food loss and waste (FLW) and 2.1 Gt CO2e of FLW-associated greenhouse gas (GHG) emissions occurred globally. Numerous opportunities for reducing food loss and waste—as well as the associated unnecessary emissions—exist, so supply chain analysis to target the most important loss points in a supply chain and waste points among consumers is needed to identify priorities. The challenge is to target 50% reductions in food loss and waste in five major supply chains where both greenhouse gasses and loss or waste are high, such as beef, dairy, and intensive fruit and vegetable production.